Assessing the compliance of systematic review articles published in leading dermatology journals with the PRISMA statement guidelines: A systematic reviewCapsule Summary - Buket Gundogan, BSc (Hons); Naeem Dowlut, BSc (Hons); Shivanchan Rajmohan, BSc (Hons); Mimi R. Borrelli, MBBS, MSc; Mirabel Millip, MBBS; Christos Iosifidis, BSc (Hons); Yagazie Z. Udeaja, BSc (Hons); Ginimol Mathew, BSc (Hons); Alexander Fowler, BSc (Hons); Riaz Agha, BSc (Hons) (Elsevier, 2020)
Background: Reporting quality of systematic reviews and meta-analyses is of critical importance in dermatology because of their key role in informing health care decisions. Objective: To assess the compliance of systematic reviews and meta-analyses in leading dermatology journals with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement guidelines. Methods: This review was carried out in accordance with PRISMA guidelines. Included studies were reviews published across 6 years in the top 4 highest-impact-factor dermatology journals of 2017. Records and full texts were screened independently. Data analysis was conducted with univariate multivariable linear regression. The primary outcome was to assess the compliance of systematic reviews and meta-analyses in leading dermatology journals with the PRISMA statement. Results: A total of 166 studies were included and mean PRISMA compliance across all articles was 73%. Compliance significantly improved over time (β = .016; P = <.001). The worst reported checklist item was item 5 (reporting on protocol existence), with a compliance of 15% of articles. Conclusion: PRISMA compliance within leading dermatology journals could be improved; however, it is steadily improving.